MOLECULAR MODELING AND DRUG DISCOVERY OF POTENTIAL INHIBITORS FOR ANTI CANCER TARGET GENE PLK- POLO LIKE KINASE1 - S.BHAGAVATHI,; DR. ANIL PRAKASH,; DR.GULSHAN WADHWA, (International Journal of Pharma and Bio Sciences, 2014)
The oncological target Polo like kinase 1 plays a key role in mitosis and cytokinesis .PLK 1 is associated with tumorigenesis and belongs to a family of disease relevant protein kinases that can be targeted by different drugs. It represents a promising approach for the development of novel anticancer therapies. Identification of novel inhibitors in polo like kinase 1 is important as it is closely correlated with malignant proliferative diseases such as lung cancer. PLK 1 is found to be over expressed in many lung cancer cell lines and human lung tumors. Thus, it is proposed that PLK1 might be a valuable diagnostic marker and a potential therapeutic target for lung cancer. However, only a few PLK1 inhibitors are in clinical development. Therefore, there is a high level of interest and an increasing effort to identify and develop novel PLK1 inhibitors. We have listed out 4 such potential inhibitors which could be promising inhibitors for Polo Like Kinase 1 namely Gemcitabine , paclitaxel, vorinostat and Etoposide. The interaction between the predicted structure of Polo like kinase 1 and its potential inhibitor is analysed in silico by Autodock. This study provides an insight into the structure of polo like kinase-1 in lung cancer and also gives an idea about potential sites responsible for inhibitory action that could further be substantiated by experimental investigations. This study facilitates initiation of the drug discovery process for polo like kinase 1 to present the scientific community with better inhibitors and/or drugs.